REACT LEARNING MODEL TO IMPROVE LEARNING OUTCOMES OF SOCIAL SCIENCES IN GRADE V OF STATE ELEMENTARY SCHOOL 25 LUBUKLINGGAU - ROHMI YANSA (Teaching and General Education Studies, 2026)
This study aimed to improve the Social Studies learning outcomes of Grade V students at State Elementary School 25 Lubuklinggau through the implementation of the REACT learning model. The research employed a Classroom Action Research design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were 20 Grade V students. Data were collected using tests, observations, and documentation. The results showed a significant improvement in students’ learning outcomes after the application of the REACT model. In Cycle 1, the average post-test score increased to 74.81, with 70.73% of students achieving the Minimum Mastery Criteria. Further improvement was observed in Cycle 2, where the average post-test score reached 80.19 and 85.19% of students achieved learning mastery. These findings indicate that the REACT learning model effectively enhances students’ understanding, engagement, and academic achievement in Social Studies learning. Therefore, the REACT learning model is recommended as an alternative instructional strategy to improve the quality of Social Studies learning at the elementary school level.